2013
DOI: 10.1186/1756-0500-6-306
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hyperkalemia in patients with moderate chronic kidney disease initiating angiotensin converting enzyme inhibitors or angiotensin receptor blockers: a randomized study

Abstract: BackgroundAngiotensin-converting enzyme inhibitors and angiotensin II receptor blockers are renoprotective but both may increase serum potassium concentrations in patients with chronic kidney disease (CKD). The proportion of affected patients, the optimum follow-up period and whether there are differences between drugs in the development of this complication remain to be ascertained.MethodsIn a randomized, double-blind, phase IV, controlled, crossover study we recruited 30 patients with stage 3 CKD under restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Our observed rates of hyperkalemia generally coincide with those reported in the general population without risk factors (≈2%) . However, the increased risk with lower eGFR is also consistent with previous reports, where rates may be as high as 40% . This variation in hyperkalemia risk supports recommendations that tailor monitoring strategies to the individual patient, such as that put forth by KDOQI in 2004 .…”
Section: Discussionsupporting
confidence: 91%
“…Our observed rates of hyperkalemia generally coincide with those reported in the general population without risk factors (≈2%) . However, the increased risk with lower eGFR is also consistent with previous reports, where rates may be as high as 40% . This variation in hyperkalemia risk supports recommendations that tailor monitoring strategies to the individual patient, such as that put forth by KDOQI in 2004 .…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, and alike a previous report [12], we found that the hyperkalemia risk associated to ACEi or MRA were similar, and higher than that of the risk associated to ARB or potassium-sparing diuretics. Our estimates are therefore in line with some [35,36], but not all [23] trials suggesting that ACEi have stronger effect in raising potassium than ARBs. Recent RCTs suggest that the use of potassium binder medications may allow the use of RAASi in patients prone to hyperkalemia [37][38][39][40], but the long-term benefit of such strategies on clinical outcomes is yet to be demonstrated.…”
Section: Discussionsupporting
confidence: 89%
“…Means to help predict a predisposition include estimating the GFR, baseline serum potassium check, and obtaining information on the intake of dietary potassium, supplements, and drugs that raise potassium [87]. Serum potassium needs to be measured after the first week and first and second months following the initiation of therapy; should hyperkalemia develop, prompt recognition of cardiac dysrhythmias is necessary to manage and optimize outcomes [87,88]. Hyperkalemia may be totally asymptomatic.…”
Section: Angiotensin-converting Enzyme Inhibitors and Angiotensin Recmentioning
confidence: 99%